1999
DOI: 10.1143/ptps.136.1
|View full text |Cite
|
Sign up to set email alerts
|

Trans-Planckian Redshifts and the Substance of the Space-Time River

Abstract: Trans-Planckian redshifts in cosmology and outside black holes may provide windows on a hypothetical short distance cutoff on the fundamental degrees of freedom. In cosmology, such a cutoff seems to require a growing Hilbert space, but for black holes, Unruh's sonic analogy has given rise to both field theoretic and lattice models demonstrating how such a cutoff in a fixed Hilbert space might be compatible with a low energy effective quantum field theory of the Hawking effect. In the lattice case, the outgoing… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
174
2
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 167 publications
(178 citation statements)
references
References 40 publications
1
174
2
1
Order By: Relevance
“…In more realistic models, the number N of patches should change in time, either by a fundamental process of discrete geometries being refined [32,33], or by an approximation procedure akin to adaptive mesh refinement that maintains the decomposition into isotropic patches as a good model. (A time-dependent number of degrees of freedom is a general problem, studied for instance in [34,35,36,37,38]. )…”
Section: Classical Modelmentioning
confidence: 99%
“…In more realistic models, the number N of patches should change in time, either by a fundamental process of discrete geometries being refined [32,33], or by an approximation procedure akin to adaptive mesh refinement that maintains the decomposition into isotropic patches as a good model. (A time-dependent number of degrees of freedom is a general problem, studied for instance in [34,35,36,37,38]. )…”
Section: Classical Modelmentioning
confidence: 99%
“…As before we take the field to be in the free fall vacuum state. A number of studies have demonstrated that in this state, to leading order in κ/Λ, models with UV dispersion reproduce the relativistic result that the outgoing modes at infinity are thermally populated at the Hawking temperature [30,31,32,33]. To evaluate the entanglement entropy we need to know whether thermality extends to the near-horizon modes that contribute to the entropy.…”
Section: Dispersion Induced Cut-offmentioning
confidence: 99%
“…The validity of these assumptions is unclear; this is known as the trans-Planckian question of inflationary cosmology [4].…”
Section: Introductionmentioning
confidence: 99%